Hambatan Desa Munggu Sebagai Desa Wisata Di Kabupaten Badung - Purwaningsih, Ni Putu Enik; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
This research was conducted in Munggu village, Mengwi subdistrict, Badung Regency. This research aims t o identify the obstacles experienced by Munggu village as a tourism village in Badung regency . This research used qualitative method, which prefers the descriptive data or the data in the form of sentences instead of numbers. This data was obtained through observation, interviews, literature study and documentation. The data obtained were analyzed using the concept of obstacles . The results of this study indicate tha t obstacles experienced by Munggu village as a tourism village in Badung regency consists of tw o types of obstacles, internal obstacles and external obstacles. Internal obstacles are related about the tourism product that is not maximized yet, limited funds and lack of village facilities completeness, managerial organization that is not optimal, and community participation is still lacking. Meanwhile, external obstacles are related about to the absence of standardization from the government for tourism villages, the role of local government is still lacking and Munggu tourism village has not been incorporated in the network of tourism villages .   Keywords : Barriers, Tourism Village, Development Strategy